2009
DOI: 10.2340/00015555-0680
|View full text |Cite
|
Sign up to set email alerts
|

Latent Dystrophic Subcutaneous Calcification in Patients with Chronic Venous Insufficiency

Abstract: Dystrophic calcification in the skin occurs in association with a variety of disorders. To determine the association between subcutaneous calcification and chronic venous insufficiency, X-ray examinations were performed in 20 patients with chronic venous insufficiency and in 20 control subjects to detect latent calcification in their lower legs. Of the 20 patients, 13 (65%) had subcutaneous calcification, and the prevalence appeared to increase with disease duration, while only 4 control subjects (20%) had min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
0
11
0
2
Order By: Relevance
“…Although BG are extensively investigated and used for wound-healing applications, the studied glass compositions have already been shown to form a layer of hydroxycarbonate of apatite (HCA) on their surface [ 69 , 82 ]. However, just one layer of HCA can inhibit hemostasis, and Ca deposits can impede the healing of ulcers [ 69 , 83 , 84 , 85 , 86 ]. In this context, Jung and Day [ 87 ] produced borate glass fibers scaffolds by the melt blow technique, containing one or more trace elements of Cu, F, Fe, Mn, Mo, Ni, Sr, and Zn, chemically dissolved in the material at a concentration of about 0.05 and 10% by weight.…”
Section: Wound Healingmentioning
confidence: 99%
“…Although BG are extensively investigated and used for wound-healing applications, the studied glass compositions have already been shown to form a layer of hydroxycarbonate of apatite (HCA) on their surface [ 69 , 82 ]. However, just one layer of HCA can inhibit hemostasis, and Ca deposits can impede the healing of ulcers [ 69 , 83 , 84 , 85 , 86 ]. In this context, Jung and Day [ 87 ] produced borate glass fibers scaffolds by the melt blow technique, containing one or more trace elements of Cu, F, Fe, Mn, Mo, Ni, Sr, and Zn, chemically dissolved in the material at a concentration of about 0.05 and 10% by weight.…”
Section: Wound Healingmentioning
confidence: 99%
“…Tokoro et al (10) , on the other hand, used PA and lateral tibial radiographs for the diagnosis of lipodermatosclerosis. They confirmed the presence of skin and subcutaneous tissue calcifications in 65% of patients with lipodermatosclerosis, which were either punctate-type calcifications or merged into conglomerates referred to by the authors as trabecular calcifications (10) . In their paper, the authors confirmed a large percentage of calcifications in patients with advanced CVI, which was also confirmed by HFU.…”
Section: Radiographymentioning
confidence: 99%
“…Two patterns of calcification are encountered on plain radiographs: punctate and trabecular/reticular types ( Fig. 3 ) ( 7 ). The incidence of calcification correlates with disease duration and severity.…”
Section: Dystrophic Calcificationmentioning
confidence: 99%
“…The incidence of calcification correlates with disease duration and severity. Patients with longer disease duration present primarily with the trabecular type ( 7 ). Besides, the presence of these calcification causes poor wound healing.…”
Section: Dystrophic Calcificationmentioning
confidence: 99%